Incidence and risk factors of anthracycline-induced cardiotoxicity in long-term survivors of pediatric cancer: A population based cohort study - Prathana Nathan; Ketan Kulkarni; Tamara MacDonald (Pediatric Hematology Oncology Journal, 2022)
Background: Population-based data on the incidence of anthracycline-induced cardiotoxicity (AIC) in long-term survivors of childhood cancer is limited. This study will report the incidence and risk factors for AIC in long term survivors of pediatric cancer. Material and methods: A retrospective population-based study was conducted using (i) patient charts (ii) oncology database at the IWK Health Centre. All pediatric oncology patients treated with anthracycline on or before December 2014 and followed in the long-term follow up were included. Cardiotoxicity was defined as an ejection fraction (EF) < 50% and/or a fractional shortening (FS) < 27% in any echocardiogram or comparable cardiac imaging and/or symptomatic cardiotoxicity. Pearson's Chi-Square and Fisher's exact were used to determine the relationship of cardiac changes to various risk factors. Results: In 184 patients, we found an incidence of AIC of 5.98%. AIC with long-term complications had a low incidence (2.17%). The mean age at diagnosis for patients with AIC was 5.55 ± 4.97 years. The follow-up time ranged from 5 to 25 years (mean = 9.06). The time from treatment to a cardiac event ranged from 0 to 15 years (mean = 3.82). Our study found that bone marrow transplant (p = 0.025) and cancer diagnosis (p = 0.039) were significantly associated with AIC. However, when only symptomatic patients were analyzed, only a cumulative dose of anthracycline ≥300 mg/m2 had a significant relationship with AIC (p = 0.017). Conclusion: The present study confirms the dose dependent AIC in long term oncology follow up patients.